2017
DOI: 10.1103/physrevphyseducres.13.020110
|View full text |Cite
|
Sign up to set email alerts
|

Students’ views about the nature of experimental physics

Abstract: The physics community explores and explains the physical world through a blend of theoretical and experimental studies. The future of physics as a discipline depends on training of students in both the theoretical and experimental aspects of the field. However, while student learning within lecture courses has been the subject of extensive research, lab courses remain relatively understudied. In particular, there is little, if any, data available that addresses the effectiveness of physics lab courses at encou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
2
35
0
5
Order By: Relevance
“…They found that students in lab courses whose primary aim was to teach physics concepts as opposed to experimentation skills came away with beliefs that were less expert-like than the ones they held when they started. 3 Labs characterized as "guided" as opposed to open-ended also showed similar negative effects. 4 Looking at student thinking To try to understand why those lab courses were failing to meet their intended aims and what might be done to make them more effective, we turned to the basic method underlying most physics education research: looking at student thinking.…”
mentioning
confidence: 71%
“…They found that students in lab courses whose primary aim was to teach physics concepts as opposed to experimentation skills came away with beliefs that were less expert-like than the ones they held when they started. 3 Labs characterized as "guided" as opposed to open-ended also showed similar negative effects. 4 Looking at student thinking To try to understand why those lab courses were failing to meet their intended aims and what might be done to make them more effective, we turned to the basic method underlying most physics education research: looking at student thinking.…”
mentioning
confidence: 71%
“…It is possible that the heavy emphasis on conceptual learning and problem solving is shaping students' personal epistemology in unintended ways in physics courses by hiding or downplaying the diverse purposes of experiments in physics. In a more recent study from Colorado Learning Attitudes about Science Survey for Experimental Physics (E-CLASS), the findings from a large national data set indicated that students in skills-focused courses showed more expert-like responses and more favorable shifts than students in either concepts-focused or both-focused courses [15].…”
Section: Discussionmentioning
confidence: 99%
“…The emphasis on experiments as tools for improving content learning in lecture is unsurprising given that many faculty have similar goals for labs [15]. However, it is somewhat surprising given the small amount of evidence that lab courses are helpful for learning concepts [16], and some studies suggest simulations may support conceptual learning better than hands-on experiments [17].…”
Section: B Finding: Experiments As Supplemental Learning Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini perlu dilakukan untuk membantu calon guru fisika dalam menyelesaikan soal fisika karena nantinya mereka akan menghadapi penyelesaian soal ketika mengikuti perkuliahan ataupun dalam menyelesaikan studi mereka. Karena cara pandang mahasiswa terhadap fisika mempengaruhi mereka dalam memahami konsep fisika dan keberhasilan dalam mata kuliah fisika (Wilcox & Lewandowski, 2017).…”
Section: Pendahuluanunclassified